Comparative Antioxidant, Antimicrobial and Phytochemical Assesments of Leaves of Desmostachya bipinnata L. Stapf, Hordeum vulgare L. and Drepanostachyum falcatum (Nees) Keng f. - Nepal, Pragya; Singh, Minu; Baniya, Amina; Singh, Sushma; Sainju, Hari Krishna; Shrestha, Rajani (Nepal Journal of Biotechnology, 2019)
Nepal is rich in varieties of religious plants. The locally used religious plants also carry medicinal importance. Desmostachya bipinnata L. Stapf, Hordeum vulgare L. and Drepanostachyum falcatum (Nees) Keng f. are three plants belonging to the family Poaceae having religious significance in different practices of Hinduism. They were also used as traditional medicines by our ancestors but nowadays they are underutilized. In this research, our core objective was to validate the traditional assumption of use of these plants in medicinal purposes by carrying out the assessments like antimicrobial assessment, antioxidative assessment and phytochemical assessment. Methanolic extracts produced from leaves of all three plants were examined for antimicrobial activities through agar well diffusion method. The same extracts were also assessed for determining their antioxidative potentials with the use of DPPH (1, 1-diphenyl-2-picryl hydrazyl) free radical scavenging assay followed by qualitative phytochemical analysis and GCMS (Gas Chromatography Mass Spectroscopy). Most promising antimicrobial activity was shown by Desmostachya bipinnata L. against Salmonella typhimurium and Staphylococcus aureus, Drepanostachyum falcatum (Nees) Keng f. against Salmonella typhimurium and Klebsiella pneumoniae and Hordeum vulgare L. against Salmonella typhmurium and Staphylococcus aureus. The antioxidant activity of the plant extracts were observed in descending order of Hordeum vulgare L.>Desmotachya bipinnata L. > Drepanostachyum falcatum (Nees) keng f. and phytochemical assessment of the extracts indicated the presence of alkaloids, glycosides, sterols, Triterpenes, Saponins, Flavonoids, Coumarins, Phlobatanin and reducing sugars. Through this project, we can clarify that the above mentioned plants have bioactive compounds which contributed for the presence of antimicrobial and antioxidative property in the plants.